Territórios da formação docente: o entre-lugar da cultura - Oliveira, Vânia Fortes de (2007)
This researche was presented to the Program of Educational Postgraduation, Master level of Federal University of Santa Maria (UFSM) Education Center, in Formation Line, Knowledge and Professional Development. The territory of the educational formation interest is presented in the research from the perspective of the auto formation. It is understood by me as a process that is in constant changing and happens in several amongplaces. The concept of culture is presented as everything that concerns the human life in its most different forms. The discussion of the culture in Education assumes a character of escape from the instrumental reason and starts being thought as self-care. The formation is seen as something that escapes from the rational and technical domain, because just the professional formation does not guarantee the teacher s action. I believe that this fact has to do with the teacher s subjective construction as person and personnal knowledge. This way, the researche has a theoretical dialogue with the originating information from the documental analysis taken from the research done by the Education and Research National Institute (MEC/ INEP) associated with the United Nations Organization for the education, science and the culture (UNESCO), called Profile of Brazilian Teachers: what they do, what they think about, what they wish... The emphasis of the analysis is about the chapter O Perfil dos Professores Brasileiros (Brazilian teachers profile), with special attention to the sub-chapter Os professores e suas práticas culturais (The professors and their cultural practices). The choice of the material was made second the large quantity and relevance of the research as form of contribution to the of the cultural formation discussion of Brazil s teachers. My research question is the inquiry of the teacher s cultural formation aspects, having it as a subjective construction that remits to the imaginary social field, second Cornelius Castoriadis. As objective, I chose the approach with the Brazilian teachers cultural formation as understanding form about the process of auto formation, establishing a dialogue with the concept of self-care by Michel Foucault. I believe that the teacher s experiences can produce sense, from the re-significance of it during all the formation process as a professional. The documentary analysis of the research about the Brazilian teachers profile enabled the understanding of the conditions in wich they are found and the way they are related with the culture. It became possible to verify that the socio-economic conditions favorise, in so many ways, its practices. In what concerns the teachers preferences, in general way, the wishes go to the social imaginary and to the population s practices in general, depending of the localities of their adress and of their age. However, it reveals the choices diversity from the cultural plurality. Finally, the contribution of the self-care concept is a possibility in the sense to take care of itself (teacher) to, then, take care of another (student)